Analytical and experimental study of beam bending vibration - AL-NAJJAR, IYAD F.; Kollár, László E.; Jálics, Károly (Design of Machines and Structures, 2024)
This study presents free bending vibration analysis of beams of glass epoxy material. The analytical and the modal model (experimental) methods were used to conduct the investigation. The experiment represents basic concepts of the modal model analysis method, which allows us to find the beam’s natural frequencies and vibrational mode shapes. The analytical solution was found using Maple and compared to the frequencies obtained experimentally.